PERDAMAIAN DALAM KONTEKS PLURALITAS INDONESIA: SEBUAH ANALISIS ETIS-TEOLOGIS - Made Nopen Supriadi; Malik Malik (Sekolah Tinggi Teologi Sabda Agung, Surabaya, 2022)
Pluralism is the color of Indonesia. Pluralism has the potential to cause conflict if it is seen as a threat, but plurality becomes a wealth if it accepts differences. The history of Indonesia shows that the presence of differences does not cause significant friction, in fact friction begins to occur when there is an action in pluralism trying to generalize all situations to be the same. The majority group wants to generalize their views and apply their views, so the attempt to harmonize culture creates conflict. This research applies the literature study method in the form of descriptive analysis. The results of this study show the situation of life in Plural Indonesia and solutions to build peace in the context of the plurality of life in Indonesia.